2017
DOI: 10.1016/j.biomaterials.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Combined influence of biophysical and biochemical cues on maintenance and proliferation of hematopoietic stem cells

Abstract: Homeostasis of hematopoietic stem and progenitor cells (HSPC) is controlled by a combination of biochemical and biophysical environmental cues in the bone marrow (BM) niche, where a tight balance of quiescence and proliferation of HSPC is maintained. Specifically, alongside soluble factors and extracellular matrix (ECM) proteins, spatial confinement and ECM stiffness have been recognized to be critical for regulation of HSPC fate. Here we employ a modular, glycosaminoglycan (GAG)-based biohybrid hydrogel syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 50 publications
2
43
0
Order By: Relevance
“…In the current study, a decrease in proliferation under spatial confinement was observed for all cell lines tested over one to three days in the confiner. Similar results were found by [49], who reported a higher frequency of quiescent cells upon confinement within a stiff 3D matrix. These results also corroborate those obtained using PDMS set-ups [50,51] and atomic force microscopy (AFM) [52], where it was reported that confinement delays mitotic progression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, a decrease in proliferation under spatial confinement was observed for all cell lines tested over one to three days in the confiner. Similar results were found by [49], who reported a higher frequency of quiescent cells upon confinement within a stiff 3D matrix. These results also corroborate those obtained using PDMS set-ups [50,51] and atomic force microscopy (AFM) [52], where it was reported that confinement delays mitotic progression.…”
Section: Discussionsupporting
confidence: 89%
“…We anticipate that this device could be a valuable tool for the fundamental understanding of the effect of cell confinement on various hallmarks of cancer progression and resistance, and in particular to decipher the role of nuclear mechanosensitivity. Links between cell resistance to treatment and mechanical stimuli have been highlighted recently [49,67,68]. Such mechanical cues could hence lead to new therapeutic approaches [69] that could be tested using such systems.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Moreover, an osmotic compression, stress of very different origin and sensing which could arise in vivo due to accumulation of oncotic pressure [27], also leads to similar modulation of chemotherapeutic. There are now evidences that quiescence is one major mechanism leading to drug resistance [28] and that mechanics can turn cells towards quiescence [8,29]. However, to our best knowledge, no quantitative models linking mechanics to drug resistance, through a direct modulation of proliferation, have been proposed so far.…”
mentioning
confidence: 99%
“…A number of recent studies have focused on mimicking the BM niche characteristics in vitro by creating 3D culture systems that incorporate, along with growth factors and cytokines, different biomaterials to provide a range of biophysical cues in an attempt to induce symmetric cell divisions of HSCs in vitro [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Biomaterial elasticity is currently recognized to affect the fate of HSPCs [ 33 , 34 , 35 , 36 ]. In 2010, Holst et al reported that the proliferation of repopulating HSCs was enhanced when cells were cultured on top of soft tropoelastin-coated plates compared to cells cultured on top of control plates without tropoelastin [ 33 ].…”
Section: Introductionmentioning
confidence: 99%